Level of Knowledge of Medical School Students About Basic Life Support - Muhammad Aiman bin Harun; Pontisomaya Parami; I Kadek Agus Heryana Putra; Adinda Putra Pradhana (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Basic Life Support is one of the most important knowledge for doctors and medical students to master. Cardiac arrest can strike anyone without any underlying symptoms. Basic life support can help reduce mortality from cardiac arrest if performed quickly and correctly. This study aims to determine the level of knowledge of basic life support in undergraduate medical students at the Faculty of Medicine, Udayana University because of the need to increase basic life support knowledge in medical students. This research is a quantitative descriptive study with a cross-sectional research design. This research was conducted at the Faculty of Medicine, Udayana University, which was carried out in October 2022. This research uses a stratified random sampling technique which uses primary data from respondents. The population of this study was 1.494 semester students of the medical education study program at the Faculty of Medicine, Udayana University. The research sample was 258 samplee. Data collection using a questionnaire. Analysis of research data using univariate analysis in the form of descriptive frequency distribution, and percentage data. The research results showed that the majority of students at the Faculty of Medicine, Udayana University, had sufficient knowledge about Basic Life Support, 38 (14.7%). The sufficient level of knowledge about Basic Life Support was in the 2020 academic year class of 19 (7.36%), and the level of knowledge about Basic Life Support was obtained based on the experience of university organizations as many as 21 (8.14%). There is still room for improvement to increase the level of knowledge about BLS among the participants. basic life support courses can be integrated into medical students for a fixed period of time to ensure knowledge and skills in basic life support are accessible to every medical student. Keywords: Basic life support, Cardiopulmonary resuscitation, Knowledge, Medical student